Arsenicosis in Bangladesh: prevalence and sociodemographic correlates - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
Arsenic contamination in drinking water has created concern for its potential health effects but our understanding of the risk factors of arsenicosis remains limited. This study assesses the prevalence of and soeio-demographic differentials in arsenic-associated skin lesions in a rural community in Bangladesh. Data were collected from a village \-Vhere BRAC had both health surveillance system and community-based arsenic mitigation project since 1999. A total of I ,654 residents in the study village were examined to detect arsenic-associated lesions on their skin in May 2000. The socio-demographic infom1ation \\'as extracted from the surveillance system database covering the village. Finding reveals that nearly 2. 9% of the study population had clinical manifestations of arsenic poisoning. The prevalence of arsenicosis was associated with age, sex, education and the economic status of the household. Multivariate analysis identified age and economic status as significant predictors of arsenicosis controlling for education and gender. The study concludes that arsenic contan1ination in drinking water became a major public health problem in the affected communities although the burden of disease \\·as spread unevenly and fell most heavily on certain groups. A detailed understanding of the distribution of arsenicosis is needed in designing an effective mitigation project.